1985
DOI: 10.1029/jc090ic05p09089
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between a continuous 3‐year current‐meter observation at the sill of the Yucatan Strait, satellite measurements of Gulf Loop Current area, and regional sea level

Abstract: From October 1977 through November 1980 a current‐meter mooring was maintained in the Yucatan Strait. The meter was moored halfway between Mexico and Cuba, 145 m above the sill or in 1895 m of water. Motions of low frequency (<14−1 cycles/day) are oriented approximately parallel to the isobaths, 021°–030° true. Net drift for 3 years is to the SSW at an average velocity of 1.8 cm/s. Sustained southward flows at intervals of 8 months, which persisted for several months each, have average velocities of 5 cm/s, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
61
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 17 publications
13
61
0
2
Order By: Relevance
“…by Maul et al, [1985] and Maul and Vukovich [1993] to insufficient sampling in the YC. The authors suggested that a longer data set was required to further test and validate Maul's [1977] theory.…”
Section: Maulmentioning
confidence: 99%
“…by Maul et al, [1985] and Maul and Vukovich [1993] to insufficient sampling in the YC. The authors suggested that a longer data set was required to further test and validate Maul's [1977] theory.…”
Section: Maulmentioning
confidence: 99%
“…5 have been smoothed since derivatives are noisy. We note first that there is a significant correlation (R=0.4) between changes in the LC area and the deep outflow below 800 m, so that increase in the deep southward outflow is an indication of growing LC, as proposed in [1]. Also shown in Fig.…”
Section: B Loop Current Variations and Yucatan Channel Transportmentioning
confidence: 80%
“…4) are often found. As hypothesized in [1] and shown in [3], the deep return transport is expected to correlate with changes in the LC extension (not with the area averaged elevation L itself, but with its derivative). Therefore, we calculate the daily change in the LC elevation, i.e., the derivative ∆L/∆t; the distribution of this derivative as a function of the deep outflow is shown in Fig.…”
Section: B Loop Current Variations and Yucatan Channel Transportmentioning
confidence: 98%
See 2 more Smart Citations